Lectotypification of Impatiens acuminata Benth. ex Hook.f. & Thomson and notes on its geographical distribution - Deori, Chaya; Tham, Bladimir Bajur Theodore; Talukdar, Satya Ranian; Adamowski, Wojciech; Gogoi, Rajib (Biodiversity: Research and Conservation, 2018)
Impatiens acuminata Benth. ex Hook.f. & Thomson, endemic to Meghalaya in North-Eastern India, is lectotypified here. The species was collected/observed only five times in the 20th century. A detailed description and photographic illustrations based on live plant material is provided for its easy identification along with its comparison to closely related species I. parkinsonii C. E. C. Fisch. Geographical distribution, conservation status and horticultural potentials of the species are also discussed.